2017
DOI: 10.1038/s41598-017-15396-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Predictors and Outcome of Prosthesis-Patient Mismatch after Transcatheter Aortic Valve Replacement: a Systematic Review and Meta-analysis

Abstract: The aim of this study was to investigate the incidence, predictors and outcome of prosthesis-patient mismatch (PPM) following transcatheter aortic valve replacement (TAVR). A total of 30 articles incorporating 4,691 patients were identified. The pooled incidences of overall, moderate and severe PPM following TAVR were 33.0%, 25.0% and 11.0% respectively. Medtronic CoreValve (MCV) had lower incidence of overall (32% vs: 40%, P < 0.0001) and moderate (23% vs 32%, P < 0.0001) than Edwards Sapien (ESV). PPM was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…In line with previous studies, we found that a lower EF and a history of myocardial infarction are associated with a higher incidence of PPM. A dysfunctioning LV may eject a smaller stroke volume than required to adequately open the aortic valve leaflets during ventricular ejection and, accordingly, contribute to EOA reduction.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies, we found that a lower EF and a history of myocardial infarction are associated with a higher incidence of PPM. A dysfunctioning LV may eject a smaller stroke volume than required to adequately open the aortic valve leaflets during ventricular ejection and, accordingly, contribute to EOA reduction.…”
Section: Discussionsupporting
confidence: 93%
“…This could also be explained by inappropriate valve sizing and mal‐position which was associated with TAVI procedure during the early induction years. This trend might be reversing with increasing operator experience, aggressive post dilation and improved hemodynamic performance of the newer generation prostheses . However, the timing of assessment of paravalvular leak differed across studies although studies commonly used echocardiography to diagnose it.…”
Section: Discussionmentioning
confidence: 99%
“…This trend might be reversing with increasing operator experience, aggressive post dilation and improved hemodynamic performance of the newer generation prostheses. [33][34][35] However, the timing of assessment of paravalvular leak differed across studies although studies commonly used echocardiography to diagnose it.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…There have been multiple, and sometimes disparate, reports on the definitions, measurements, and prognostic value of PPM following SAVR and TAVR 25‐42 …”
Section: Prosthesis Patient Mismatchmentioning
confidence: 99%